Ethical Dilemma and Obedience Pressure: Their Impact on Audit Decisions with Locus of Control as a Moderating Variable - Kuntoro, Agus (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
This study examines the influence of professional ethics and obedience pressure on audit decisions, with locus of control as a moderating variable. The background of this research is driven by the increasing complexity of auditors’ decision-making processes, particularly when facing ethical dilemmas and external pressures in professional settings. The aim of this study is to analyze whether professional ethics and obedience pressure affect audit decisions and to test the moderating role of locus of control. This research employs a quantitative approach using primary data collected through questionnaires distributed to auditors working in Public Accounting Firms. A total of 207 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that professional ethics and obedience pressure have a positive and significant effect on audit decisions. However, locus of control does not significantly moderate the relationship between professional ethics and audit decisions, nor between obedience pressure and audit decisions. These findings indicate that external factors, particularly obedience pressure, tend to be more dominant than internal control in influencing auditors’ decisions. In conclusion, strengthening professional ethics and maintaining auditor independence are crucial in improving audit decision quality. The study implies that organizations should enhance ethical training and create supportive environments to minimize undue pressure.